2011
DOI: 10.3343/kjlm.2011.31.3.219
|View full text |Cite|
|
Sign up to set email alerts
|

Heterogeneous Spectrum of CFTR Gene Mutations in Korean Patients with Cystic Fibrosis

Abstract: BackgroundCystic fibrosis (CF) is one of the most common hereditary disorders among Caucasians. The most common mutations of the cystic fibrosis transmembrane conductance regulator (CFTR) gene have been well established among Caucasian populations. In Koreans, however, there are very few cases of genetically confirmed CF thus far, and the spectrum of mutations seems quite different from that observed in Caucasians.MethodsIn the present study, we describe the cases of 2 Korean CF patients, present sequencing re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 30 publications
3
16
0
Order By: Relevance
“…In the present study, the most common mutation in Caucasians, F508del, was not detected; R553X, a much less common mutation accounting for 0.7% of CF patients in Caucasians, was present in patient 2. Q98R is a mutation that was first reported in Southern France and is primarily detected in Koreans and Japanese, with a detection rate as high as 18.8% . This mutation was detected in two of our Chinese patients; one a homozygote born of consanguineous parents and the other a heterozygote.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…In the present study, the most common mutation in Caucasians, F508del, was not detected; R553X, a much less common mutation accounting for 0.7% of CF patients in Caucasians, was present in patient 2. Q98R is a mutation that was first reported in Southern France and is primarily detected in Koreans and Japanese, with a detection rate as high as 18.8% . This mutation was detected in two of our Chinese patients; one a homozygote born of consanguineous parents and the other a heterozygote.…”
Section: Discussionmentioning
confidence: 54%
“…Q98R is a mutation that was first reported in Southern France 21 and is primarily detected in Koreans and Japanese, with a detection rate as high as 18.8%. 22 This mutation was detected in two of our Chinese patients; one a homozygote born of consanguineous parents and the other a heterozygote. The rest of the mutations identified in the present study, are only reported in a few studies and mostly specific to Asians, as documented in HGMD.…”
Section: Discussionmentioning
confidence: 74%
“…In order to study the spectrum of CF in Korean patients, we reviewed the previously identified cases of CF at our institution (n = 5) (3818) and in the literature (n = 7) (4567919), in addition to the cases analyzed in this study (n = 2). Clinical and radiologic features of these patients were summarized in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…Cystic fibrosis is the most frequently occurring life‐limiting autosomal recessive disorder among Caucasians populations, with a carrier frequency of about 1:25, resulting in a disease incidence of 1 in 2,500 live births . However, CF is quite rare in Asian populations, and an epidemiological study of the Japanese population found the incidence of CF to be about 1 in 350,000 . In China, there are no epidemiological statistics in incidence of this disease.…”
Section: Discussionmentioning
confidence: 99%
“…1 However, CF is quite rare in Asian populations, and an epidemiological study of the Japanese population found the incidence of CF to be about 1 in 350,000. 2 In China, there are no epidemiological statistics in incidence of this disease. There have been only 36 cases report from 1974 until the present.…”
Section: Discussionmentioning
confidence: 99%